Description of a new genus and species (Eutardigrada: Richtersiidae) from Colombia, with comments on the family Richtersiidae - Lisi, Oscar; Londoño, Rosana; Quiroga, Sigmer (Zootaxa, 2020)
The new genus of the macrobiotoid family Richtersiidae Guidetti, Rebecchi, Bertolani, Jönsson, Kristensen & Cesari, 2016 Crenubiotus gen. nov. is described, based on Crenubiotus crenulatus comb. nov. (Richters, 1904a) and on Colombian specimens formerly attributed to Macrobiotus cf. crenulatus and here described, after re-examination, as Crenubiotus revelator sp. nov. The new genus is characterised by an additional ventral thickening on the anterior portion of the ventral lamina, dorsal apophysis absent or very reduced, modified stylet furcae, claws equal in structure to those of Richtersius Pilato & Binda, 1989, and very probably also Adorybiotus Maucci & Ramazzotti, 1981 and Diaforobiotus Guidetti, Rebecchi, Bertolani, Jönsson, Kristensen & Cesari, 2016; and, in the known species, cuticular pores, two macroplacoids, large well dentate lunules and a characteristic egg. The new species Crenubiotus revelator sp. nov. differs from Crenubiotus crenulatus comb. nov. in having smaller cuticular pores, a medio-ventral tooth in the buccal armature, more slender buccal tube, slightly more caudal stylet supports, slightly more slender claws, and in details of the egg. The description of the new genus, and new observations on Adorybiotus, Richtersius and Diaforobiotus, allowed the authors to complete the morphological scenario within the family Richtersiidae giving further support to such family.